Gender and Australian celebrity culture - Taylor, Anthea, 1972-; McIntyre, Joanna (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This intellectually vibrant volume is the first collection to deal with Australian celebrity in ways that account for both cultural and gendered specificities, demonstrating how gendered ways of imagining Australia are reinforced and contested in celebrity representations and self-presentations. Gender and Australian Celebrity Culture engages with celebrities across a diverse range of fields - actors, journalists, athletes, comedians, writers, and television personalities - and in doing so critically reflects upon different forms of Australian fame and the media platforms and practices that sustain them. Authors in this volume engage directly with pertinent issues relating to gender and sexuality, including celebrity feminism and the generative capacity of feminist rage; normative femininity and its instability; hegemonic masculinities; and queerness and its (in)visibility. Contributors also intervene in a number of ongoing debates in media and cultural studies more broadly, including those around the politics and affordances of digital media; whiteness and Australia's colonial histories; celebrity labour; and methodologies for celebrity studies. This timely collection urges scholars of celebrity to attend further both to the gendered nature of celebrity culture and to local conditions of production and consumption. This book will be of key interest to researchers and graduate students in cultural studies, television and film studies, digital media studies, critical race and whiteness studies, gender and sexuality studies, and literary studies"--
OCLC-licensed vendor bibliographic record.
Keywords: Popular culture -- Australia; Celebrities -- Australia; Feminism -- Australia; Masculinity -- Australia; SOCIAL SCIENCE / Gender Studies